Answer:
option (2) and (5) is correct.
2) This equation has no solution.
5) Any input value for the variable will generate a false equation.
Explanation:
Given a solution to the equation,
-6( x + 5) + 3 = -2( x + 4) - 4x
⇒ –6x – 30 + 3 = –2x – 8 – 4x
⇒ –6x – 27 = –6x – 8
⇒ –27 = – 8
Which is false statement as -27 is never equal to -8.
Thus, This equation has no solution.
Also, if we substitute any value of x , then also the equality never hold.
For example lets put x = 1 in -6( x + 5) + 3 = -2( x + 4) - 4x , we get,
⇒ -6( 1 + 5) + 3 = -2( 1 + 4) - 4(1)
⇒ -6( 6) + 3 = -2(5) - 4
⇒ -36 + 3 = -10 - 4
⇒ -33 = -14
Still the value is false as -33 is never equal to -14.
Any input value for the variable will generate a false equation.
Thus, option (2) and (5) is correct.